Ultrahigh-strength steel with low carbon footprint and manufacturing method thereof
By using electric furnace-LF furnace-RH-continuous casting process and full scrap steel smelting technology in the steel plate manufacturing process, combined with specific chemical element composition design and process parameter optimization, the problem of difficulty in taking into account low carbon footprint and high-strength weight loss in the existing technology is solved, and efficient and environmentally friendly ultra-high-strength steel plate manufacturing is achieved.
Patent Information
- Application Number
- CN202311240212.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-25
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-09-25
AI Technical Summary
The prior art is difficult to improve the strength of steel plates while having low carbon footprint and high strength weight reduction performance, especially in the manufacturing process of high-strength steel for automobiles.
The low-carbon emission steelmaking production process is adopted with electric furnace-LF furnace-RH-continuous casting, and the use of full scrap steel as smelting raw material, and the solid solution and precipitation form of nitrogen is controlled through specific chemical element composition design and process parameter optimization to improve the strength and plasticity of the material.
The low-carbon footprint and high-strength weight reduction were achieved. The yield strength of the steel plate is between 700-850MPa, the tensile strength is ≥980MPa, the elongation of the fracture is ≥10%, and the cold bending performance of 180 degrees is excellent. The carbon footprint is ≤1.2kgCO2eq/kg.
Smart Images

Figure CN119685713A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a steel plate and a method for manufacturing the same, and in particular to an ultra-high strength steel and a method for manufacturing the same. Background Art
[0002] In recent years, in order to achieve vehicle body weight reduction, energy conservation and emission reduction, improve collision safety and reduce manufacturing costs, advanced high-strength steel for automobiles has been widely used. It increases the strength of steel plates to reduce the thickness of steel plates while maintaining excellent forming properties.
[0003] With the development of high-strength steel technology, we expect not only to focus on the improvement of its mechanical properties, but also to achieve high strength, weight reduction, greenness and low carbon.
[0004] The Chinese patent document with the publication number CN113215477A and the publication date of August 6, 2021, entitled "A method for preparing a low-carbon emission cold-rolled base steel strip", discloses a method for preparing a low-carbon emission cold-rolled base steel strip, the process route of which is top and bottom combined blowing converter smelting, converter slag washing to remove inclusions, slab continuous casting and hot continuous rolling to produce a low-carbon, low-silicon and boron-containing cold-rolled deep-drawn base steel coil. Although the nitrogen content in the steel is reduced by omitting the LF refining process, there is no electrode consumption in the production process, which reduces power consumption and carbon dioxide emissions.
[0005] The Chinese patent document with publication number CN115058641A and publication date September 16, 2022, and titled "A method for smelting low-sulfur, low-aluminum, high-carbon wire rod steel in an all-scrap electric furnace" discloses a method for smelting low-sulfur, low-aluminum, high-carbon wire rod steel in an all-scrap electric furnace. The method belongs to the field of metallurgical technology, which includes electric furnace smelting, LF refining, RH vacuum refining, and continuous casting processes; all scrap steel is used as the charge in the electric furnace smelting process, and the order of charging for steelmaking is ferrosilicon → carburizer → ferromanganese → other alloys → slag.
[0006] It can be seen that none of the above patent documents involve low carbon footprint technology.
[0007] Although the Chinese patent document with the publication number CN 115433855A and the publication date of December 6, 2022, entitled "Aluminum extrusion with low carbon footprint", discloses an aluminum extrusion with low carbon footprint and provides a composition of an alloy composition, about 60% of which comes from Al scrap. However, the patent document belongs to the field of aluminum alloys and does not involve steel materials with low carbon footprint. Summary of the invention
[0008] One of the purposes of the present invention is to provide an ultra-high strength steel with a low carbon footprint. The ultra-high strength steel has a unique composition design and a low carbon equivalent, and adopts a low-carbon emission steelmaking production process of electric furnace-LF furnace-RH-continuous casting. At the same time, all scrap steel is used as a smelting raw material to replace high-carbon molten iron, so that the ultra-high strength steel has the technical advantages of green and low carbon and high strength and weight reduction while meeting certain forming and bending requirements.
[0009] In order to achieve the above object, the present invention provides an ultra-high strength steel with a low carbon footprint, which contains Fe and unavoidable impurities, and further contains the following chemical elements in the following mass percentages:
[0010] C: 0.06-0.12%, Si: 0.2-0.6%, Mn: 1.7-2.3%, Mo: 0.14-0.22%, Nb: 0.02-0.05%, Ti: 0.03-0.07%, Al: 0.02-0.06%, B: 0.001-0.003%, N: 0.005-0.01%;
[0011] N distribution coefficient in the ultra-high strength steel: N 固溶 / N 析出 ≥4.
[0012] Accordingly, the present invention also provides an ultra-high strength steel with a low carbon footprint, the mass percentage of each chemical element of which is:
[0013] C: 0.06-0.12%, Si: 0.2-0.6%, Mn: 1.7-2.3%, Mo: 0.14-0.22%, Nb: 0.02-0.05%, Ti: 0.03-0.07%, Al: 0.02-0.06%, B: 0.001-0.003%, N: 0.005-0.01%; the balance is Fe and unavoidable impurities;
[0014] N distribution coefficient in the ultra-high strength steel: N 固溶 / N 析出 ≥4.
[0015] It should be noted that the ultra-high strength steel grade N 析出 The testing method is: electrolytic extraction and separation of inclusions in the material, and then the N content in the inclusions is measured as N 析出 ; N 固溶 =N 总 -N 析出 , N 总 It is the total nitrogen content in the material measured according to GB / T 20124 inert gas melting thermal conductivity method.
[0016] In the present invention, the use of an electric furnace smelting route will result in a high N content. If N exists in the matrix in the form of solid solution, it can improve the strength of the material, but if it exists in the form of precipitation, it will exist in the form of TiN inclusions. If the inclusion content is too high, it will affect the plasticity and bending properties of the material. Therefore, in the hot-rolled high-strength steel described in the present invention, while controlling the mass percentage of N to 0.0050-0.010%, it is necessary to make N exist in the form of solid solution as much as possible, and control the N distribution coefficient N 固溶 / N 析出 ≥4.
[0017] In addition, in the ultra-high strength steel of the present invention, the design principles of each chemical element are specifically described as follows:
[0018] C: In the ultra-high strength steel described in the present invention, carbon directly affects the strength, weldability and formability of the steel plate / steel strip. The higher the carbon content, the more conducive it is to improving the strength of the steel plate. If the carbon content is lower than 0.06%, the strength of the steel plate / steel strip cannot meet the target requirements; if the carbon content is higher than 0.12%, it is easy to cause the carbon equivalent to be too high, thereby deteriorating the weldability of the steel plate. Therefore, in the ultra-high strength steel described in the present invention, the mass percentage of carbon can be controlled between 0.06-0.12%. In some embodiments, the mass percentage of C can be controlled between 0.08-0.11%.
[0019] Si: In the ultra-high strength steel described in the present invention, the Si element can be dissolved in ferrite, playing a role in solid solution strengthening, and the Si element can promote the enrichment of C and Mn elements in ferrite into austenite, reduce interstitial solid solution strengthening and inhibit the formation of coarse carbides during cooling, thereby improving the ductility of the steel. However, the Si element is easily enriched and oxidized on the surface of the steel strip during annealing to form a SiO2 oxide film, which is difficult to be reduced by hydrogen and affects the surface quality. At the same time, a high Si element also has an adverse effect on the spot welding performance of the steel plate. Therefore, in the ultra-high strength steel described in the present invention, the mass percentage of silicon can be controlled between 0.2-0.6%. In some embodiments, the mass percentage of Si can be controlled between 0.3-0.6%.
[0020] Mn: In the ultra-high strength steel of the present invention, the Mn element is a solid solution strengthening element and a good desulfurizer, which is beneficial to improving the strength of the steel. At the same time, Mn can also enrich the austenite and play a stabilizing role, thereby helping to improve the plasticity of the steel. Therefore, in the ultra-high strength steel of the present invention, the mass percentage of Mn can be controlled between 1.7-2.3%, and in some embodiments, the mass percentage of Mn can be controlled between 1.9-2.1%.
[0021] Mo: In the ultra-high strength steel described in the present invention, the Mo element is a carbide element, and it also promotes the hardenability of austenite, and can cause the ferrite, pearlite and bainite transformation areas to move to the right, expanding the austenite area. However, as the Mo content increases, problems such as cold rolling edge cracks are prone to occur, and the manufacturability of the material becomes more difficult. Therefore, in the ultra-high strength steel described in the present invention, the mass percentage of Mo can be controlled between 0.14-0.22%. In some embodiments, the mass percentage of Mo can be controlled between 0.16-0.20%.
[0022] Nb: In the ultra-high strength steel of the present invention, the Nb element plays an important role in grain refinement, and the fine carbonitrides formed by the combination of Nb with C and N can delay recrystallization and prevent grain growth, which has a significant strengthening effect. Therefore, in the ultra-high strength steel of the present invention, the mass percentage of Nb can be controlled between 0.02-0.05%, and in some embodiments, the mass percentage of Nb can be controlled between 0.025-0.045%.
[0023] Ti: In the ultra-high strength steel of the present invention, Ti can fix nitrogen in the steel to form a stable compound, improve the quality of the ingot and corner crack defects, and can also form fine carbides to prevent the growth of austenite grains and refine the grains. Therefore, in the ultra-high strength steel of the present invention, the mass percentage of Ti can be controlled between 0.03-0.07%, and in some embodiments, the mass percentage of Ti can be controlled between 0.04-0.06%.
[0024] Al: In the ultra-high strength steel described in the present invention, when Al exists in a solid solution state, it can inhibit the precipitation of cementite and improve the stability of austenite. In addition, Al can form finely dispersed insoluble particles with C and N, which can refine the grains. However, if the Al content in the steel is too high, a large amount of oxide inclusions will easily form, which is not conducive to the cleanliness of the molten steel. Therefore, in the ultra-high strength steel described in the present invention, the mass percentage of Al can be controlled between 0.02-0.06%. In some embodiments, the mass percentage of Al can be controlled between 0.02-0.05%.
[0025] B: In the ultra-high strength steel described in the present invention, the main function of the B element is to improve the hardenability of the steel, thereby increasing the strength of the steel. B is easy to segregate at the austenite grain boundary, delaying the transformation of austenite to ferrite, and a lower content will have an obvious effect. At the same time, B has a good grain boundary purification effect, which can hinder the segregation of harmful elements at the grain boundary to a certain extent, thereby improving the deformation coordination of the material. However, too high a B content will cause the strength of the steel to increase, which is not conducive to obtaining good plasticity. Therefore, in the ultra-high strength steel described in the present invention, the mass percentage of B can be controlled between 0.001-0.003%. In some embodiments, the mass percentage of B can be controlled between 0.002-0.003%.
[0026] Furthermore, the ultra-high strength steel of the present invention further contains at least one of the following residual elements:
[0027] Cr≤0.05wt%;
[0028] Ni≤0.05wt%;
[0029] Cu≤0.1wt%;
[0030] V≤0.05wt%.
[0031] In the present invention, since all scrap steel is used as the smelting raw material, residual elements Cr, Ni, Cu, and V that are difficult to remove during steelmaking may be introduced into the raw material. Among them, excessive Cr and Ni elements will change the phase change law of the material, excessive Cu elements will cause the hot-rolled copper brittleness problem, and excessive V elements will also generate more precipitates to increase the strength of the material. Therefore, it is necessary to control the Cr, Ni, Cu, and V elements within the range as described above.
[0032] Furthermore, among the inevitable impurities of the ultra-high strength steel described in the present invention, P≤0.015%, S≤0.003%, and Sn≤0.01%.
[0033] In the present invention, the inevitable impurities mainly include phosphorus (P), sulfur (S), and tin (Sn). The less the content, the purer the steel and the better the performance. Among them, too high P content will weaken the grain boundaries, increase the brittleness of the material, and deteriorate the welding performance. Therefore, in the ultra-high strength steel described in the present invention, the mass percentage of P can be controlled at P≤0.015%. Excessive S content in the steel will significantly deteriorate the plasticity of the material. Therefore, in the ultra-high strength steel described in the present invention, the mass percentage of S can be controlled at S≤0.003%. Sn is also a harmful element in steel. Segregation at the grain boundaries will have an adverse effect on the toughness and plasticity of the material. At the same time, too high Sn content will also deteriorate the coating performance of the material. Therefore, in the ultra-high strength steel described in the present invention, the Sn content can be controlled to Sn≤0.01%.
[0034] Furthermore, in the ultra-high strength steel described in the present invention, the harmful element factor Hem is ≤0.018%, wherein Hem=Sn+N / 2+2S, and each chemical element is substituted into its mass percentage.
[0035] In the present invention, the harmful element factor Hem is controlled to be ≤ 0.018%, which can further ensure the bending and hole expansion performance of the material.
[0036] Furthermore, in the ultra-high strength steel of the present invention, its welding carbon equivalent C eq ≤0.28%, Ceq=C+Mn / 20+Si / 30+2P+4S, where each chemical element is substituted into its mass percentage.
[0037] In the present invention, when the mass percentages of C, Si, Mn, P and S satisfy the welding carbon equivalent C eq When the content of Al is ≤0.28%, better welding performance can be further obtained, and at the same time, the solid solution and microstructure strengthening effects of the material under this composition are better, and the material strength is higher.
[0038] Furthermore, in the ultra-high strength steel of the present invention, the mass percentage of each chemical element further satisfies at least one of the following items:
[0039] C: 0.08-0.11%;
[0040] Si: 0.3-0.6%;
[0041] Mn: 1.9-2.1%;
[0042] Mo: 0.16-0.20%;
[0043] Nb: 0.025-0.045%;
[0044] Ti: 0.04-0.06%;
[0045] Al: 0.02-0.05%;
[0046] B: 0.002-0.003%.
[0047] Furthermore, in the ultra-high strength steel described in the present invention, its microstructure includes ferrite and martensite.
[0048] Furthermore, in the ultra-high strength steel of the present invention, the volume phase ratio of martensite is 60-75%.
[0049] Furthermore, in the ultra-high strength steel described in the present invention, its yield strength is 700-850MPa, the tensile strength is ≥980MPa, the elongation at break is ≥10%, the 180-degree cold bending performance ensures no cracking under 1T conditions (i.e., no cracking when the gasket is 1 times the plate thickness), and the carbon footprint is ≤1.2kgCO2eq / kg.
[0050] In addition, another object of the present invention is to provide a method for manufacturing ultra-high strength steel with a low carbon footprint. The manufacturing method is green and efficient, and the ultra-high strength steel produced has the advantages of green and low carbon as well as high strength and weight reduction.
[0051] In order to achieve the above object, the present invention proposes a method for manufacturing ultra-high strength steel with a low carbon footprint, which comprises the following steps:
[0052] Use all scrap steel for electric furnace smelting, LF, RH and continuous casting; in the RH process, the vacuum treatment time is ≤10min, and the soft blowing after breaking the air is 15-25min;
[0053] Hot rolling and coiling;
[0054] Cold rolling;
[0055] Continuous annealing: first keep the annealing temperature at 760-820℃ for 60-200s, then cool to the rapid cooling start temperature of 650-690℃ at the first cooling rate of 3-10℃ / s, then cool to the rapid cooling end temperature of 220-260℃ at the second cooling rate of 40-80℃ / s, then keep for 200-400s for aging treatment, and finally cool to 100℃ or below at the third cooling rate of 2-10℃ / s.
[0056] The above-mentioned smelting and casting process of the present invention specifically includes: electric furnace-LF furnace-RH-continuous casting. The conventional blast furnace converter manufacturing process is relatively long. Due to the use of coke reduction iron ore method, the carbon footprint of the final product is significantly higher, basically at the level of 2.5-3.0kgCO2eq / kg. And the ironmaking and steelmaking process accounts for nearly 70% of the entire process, which is the link with the highest carbon footprint. In addition, conventional electric furnace smelting is mostly suitable for medium-high carbon and stainless steel or special steel products, and rarely involves medium-low carbon automotive high-strength steel controlled by low S\N and other impurity elements.
[0057] The present invention adopts the method of smelting all scrap steel in an electric furnace, which can greatly reduce the carbon emission level of the steelmaking and smelting process. In addition, the present invention adopts RH short vacuum time + long soft blowing time. In some embodiments, the vacuum can be evacuated to ≤100Pa and the vacuum can be maintained for ≤10min before breaking the vacuum. After breaking the vacuum, soft blowing is performed for 15-25min. The soft blowing effect is based on the slag surface just not being blown open. Then, it is left to stand for a period of time, such as 10min, and then it is suspended to the continuous casting for casting.
[0058] In the present invention, vacuum treatment can reduce the N content in molten steel, but the N content does not decrease significantly after the vacuum treatment time is too long, and long-term vacuum is not conducive to the plastic treatment of inclusions; long-term soft blowing after breaking the air can remove inclusions (mainly N- and S-compound inclusions) or achieve plastic treatment of inclusions. Therefore, the RH vacuum refining process uses short vacuum time and long soft blowing time to effectively control the inclusion and gas content. Since the N content of steel tapped from a scrap steel electric furnace is significantly higher than that of a conventional converter process, the RH treatment makes the controllable lower limit of N at the level of 50ppm, and the TiN inclusions in the molten steel can be substantially removed by the treatment so that they are basically retained in the slag.
[0059] In addition, in the manufacturing method of ultra-high strength steel described in the present invention, the deformed structure after cold rolling is kept at an annealing holding temperature of 760-820°C for 60-200s for two-phase annealing. The main purpose of this process is to recrystallize the steel plate structure after cold rolling. If the temperature is too low, the recrystallization of the steel plate structure will be incomplete, and if the temperature is too high, it will easily cause the steel plate structure to be coarse and the precipitate to decompose, thereby reducing the strength of the steel plate. Therefore, in the present invention, the annealing holding temperature is controlled at 760-820°C. Similarly, the time control of this process is also critical. If the time is too short, the recrystallization of the steel plate structure will be incomplete and the diffusion of austenite stabilizing elements (C, Mn) will be insufficient; and if the time is too long, it will easily cause abnormal conditions such as abnormally coarse grains of the steel plate structure and decomposition of precipitates. Therefore, the annealing holding time is controlled at 60-200s. In this process, the steel plate structure will be partially austenitized, and the cold-rolled deformed grains will complete the recovery recrystallization process.
[0060] In addition, the first cooling rate of the heat-insulated steel strip is controlled at 3-10℃ / s, and then slowly cooled to 650-690℃, so that part of the austenite in the steel plate structure can be first converted into ferrite, which is finer than the recrystallized ferrite in the two-phase region. This is conducive to the coordination of the soft and hard phases and the improvement of the material plasticity during the final deformation.
[0061] In addition, the second cooling rate is controlled to 40-80℃ / s, and the steel strip is quickly cooled to 220-260℃ after slow cooling by blowing air, and then kept warm for 200-400s for aging treatment. This is because if the cooling rate is too slow during this process, pearlite will appear, reducing the performance of the steel plate; and if the cooling rate is too fast, it will increase the difficulty of production and manufacturing costs. Therefore, the second cooling rate is controlled to 40-80℃ / s. The remaining austenite in the rapid cooling process is basically transformed into martensite, which greatly improves the strength. During the aging process, the quenched martensite will undergo a low-temperature tempering reaction, and the lamellar martensite obtained by quenching will undergo a small amount of decomposition and carbide precipitation, which is beneficial to improve the toughness of the material and avoid cold brittle fracture.
[0062] In addition, the steel strip after aging treatment is finally cooled to 100°C or below at a third cooling rate of 2-10°C / s, and the structure of the steel basically does not change below this temperature.
[0063] Furthermore, in the electric furnace smelting process of the ultra-high strength steel manufacturing method described in the present invention, the scrap steel used includes three types of light scrap steel, medium scrap steel and heavy scrap steel, and the weight ratio of them is light scrap steel: medium scrap steel: heavy scrap steel = (3-3.5): (1.5-2): 1.
[0064] Among them, light scrap steel refers to block-shaped or irregularly shaped finished scrap steel, trimmings and the like, with the size requirement of <300×800×1800mm and unit weight ≤0.5 ton; medium scrap steel refers to block-shaped or irregularly shaped various machine scrap steel parts, components and the like, with the size requirement of <300×500×1500mm and unit weight ≤1.0 ton; heavy scrap steel refers to block-shaped scrap steel ingots, primary rolled scrap billets and the like, with the size requirement of <300×500×1500mm and unit weight ≤2.0 ton.
[0065] Furthermore, in the LF process of the method for manufacturing ultra-high strength steel of the present invention, the slag basicity is 1.8-2.5, so that the S content is removed to within 30 ppm.
[0066] Furthermore, in the continuous casting process of the method for manufacturing ultra-high strength steel of the present invention, the superheat is controlled to be ≤30°C, the crystallizer taper is controlled to be 1.0-1.3%, and the continuous casting casting speed is controlled to be 1.0-1.5 m / min.
[0067] In the continuous casting process of the present invention, in order to ensure the smooth continuous pouring of molten steel, the molten steel needs to have a certain degree of superheat. When the superheat is higher than 30°C, it is not good for the quality of the center of the ingot, and it is easy to produce defects such as segregation and shrinkage. Therefore, in the present invention, the superheat can be controlled to be ≤30°C. At the same time, in order to better control the surface quality of the ingot and prevent defects such as small longitudinal cracks, a chamfered crystallizer is selected to improve the stress distribution and control the crystallizer taper between 1.0-1.3%; in order to take into account both production efficiency and the surface quality of the ingot, the continuous casting drawing speed is controlled between 1.0-1.5m / min. Dynamic light pressure and electromagnetic stirring are used during the casting process to better improve the segregation degree of the ingot.
[0068] Furthermore, in the hot rolling step of the method for manufacturing ultra-high strength steel of the present invention, the slab heating temperature is controlled to be 1200-1260°C, and the finishing rolling temperature is controlled to be 850-950°C.
[0069] In the hot rolling process of the present invention, the ingot can be first heated at a high temperature in the full austenite zone for a period of time so that the material softens and the components are completely diffused and uniform. After rough rolling to the intermediate billet thickness specification, the coarse structure generated in the heating furnace is broken and refined, and after further rolling to the required thickness through fine rolling, a uniform and fine recrystallized material structure is formed. When the finishing rolling temperature is less than 850°C, ferrite will precipitate before finishing rolling, resulting in a low hard phase content in the final structure, insufficient hot-rolled strength, and thus affecting the subsequent cold rolling annealing performance. Considering the upper limit control of the slab heating temperature and the temperature drop during rolling, the finishing rolling temperature generally does not exceed 950°C. Therefore, in the present invention, the finishing rolling temperature can be controlled to be 850-950°C.
[0070] Furthermore, in the coiling step of the method for manufacturing ultra-high strength steel of the present invention, the coiling temperature is controlled to be 580-660°C.
[0071] In the present invention, the hot rolling coiling temperature will also affect the hot rolling performance. When the coiling temperature is higher than 660°C, internal oxidation of Si and Mn is likely to occur on the surface of the steel plate, and a surface crushing layer will be generated by pickling, affecting the surface quality of the final product; and when the coiling temperature is lower than 580°C, the strength of the hot rolled state is too high, which will be unfavorable for the subsequent cold rolling, resulting in excessive deformation resistance, resulting in cold rolling edge cracks or poor plate shape. Therefore, preferably, in the present invention, the coiling temperature can be controlled to be 580-660°C.
[0072] Furthermore, in the cold rolling step of the method for manufacturing ultra-high strength steel of the present invention, the cold rolling reduction ratio is controlled to be 50-70%.
[0073] In the present invention, after the surface scale of the hot-rolled coil is removed by pickling, the steel plate can reach the target thickness and accumulate a certain deformation energy through 50-70% cold rolling reduction, which is more conducive to subsequent annealing and recrystallization.
[0074] The ultra-high strength steel with low carbon footprint and the method for manufacturing the same according to the present invention have the following advantages and beneficial effects:
[0075] The ultra-high strength steel with low carbon footprint of the present invention has a low carbon equivalent through a specific composition design, and controls the nitrogen to exist in a solid solution form as much as possible, and controls the nitrogen distribution coefficient N 固溶 / N 析出 ≥4, in order to improve the strength of the material and ensure the plasticity and bending properties of the material.
[0076] The method for manufacturing ultra-high strength steel with a low carbon footprint described in the present invention adopts an electric furnace all-scrap steel smelting technology route so that the prepared ultra-high strength steel has the technical advantage of being green and low-carbon, and through the control of scrap steel raw materials and steelmaking technology, the impurities and residual elements of the product are controlled at a low level so as not to affect the performance of the material.
[0077] The method for manufacturing ultra-high strength steel with a low carbon footprint described in the present invention is based on the characteristic of high N content in the electric furnace all-scrap steel smelting path. Through creative control of the RH process, N is mostly present in the material in the form of solid solution, which improves the strength of the material without damaging the local formability of the material.
[0078] In some embodiments, the yield strength of the ultra-high strength steel with a low carbon footprint described in the present invention is 700-850MPa, the tensile strength is ≥980MPa, the elongation at break is ≥10%, and the 180-degree cold bending performance ensures no cracking under 1T conditions (i.e., no cracking when the gasket is 1 times the plate thickness). At the same time, the carbon footprint is ≤1.2kgCO2eq / kg, achieving a balance between green and low carbon and ultra-high strength performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0079] Figure 1 The microstructure morphology of the ultra-high strength steel with a low carbon footprint according to Example 7 of the present invention is shown. DETAILED DESCRIPTION
[0080] The ultra-high strength steel with a low carbon footprint and the method for manufacturing the same described in the present invention will be further explained and illustrated below in conjunction with specific embodiments. However, such explanation and illustration do not constitute an undue limitation on the technical solution of the present invention.
[0081] Examples 1-20 and Comparative Examples 1-3
[0082] The ultra-high strength steels with low carbon footprint of Examples 1-20 of the present invention are all prepared by the following steps:
[0083] (1) Using all scrap steel for electric furnace smelting, LF, RH and continuous casting:
[0084] In the electric furnace smelting process, all scrap steel types are light, medium and heavy, and the scrap steel is clean. When adding scrap steel charge, 1-2 tons of light scrap steel is first laid on the bottom of the electric furnace as a substrate to prevent the impact and damage to the furnace lining when a large amount of scrap steel (especially heavy scrap steel) is poured in. During the smelting process, a large flow oxygen gun is used to blow oxygen to assist melting and dephosphorization. The end point composition of the electric furnace is controlled as follows: C≤0.05wt%, P≤0.01wt%, S≤0.03wt%, and T is controlled at the same time. 出钢 ≥1630℃. After steel is tapped, the slag is removed from the slag removal station, and the amount of slag left is controlled to be ≤40mm.
[0085] In a preferred embodiment, the weight ratio of the three types of scrap steel is light scrap steel: medium scrap steel: heavy scrap steel = (3-3.5): (1.5-2): 1.
[0086] In the LF process, after the ladle enters the LF station, Al is first added for deep deoxidation. When the sampling analysis shows that Al ≥ 0.03wt%, recarburizer, ferrosilicon and ferromanganese are added for carbon supplementation and deoxidation alloying treatment, and slag is added for slag desulfurization. The slag is lime and fluorite, the amount of lime added can be 6-8kg / t steel, and the amount of fluorite added can be 1-2kg / t steel, so that the slag basicity is preferably controlled to 1.8-2.5, so that the S content is removed to within 30ppm. After S removal is completed, the required Nb, Ti, and B alloys are added. After all the alloy components are added in place, prepare to leave the station, and at the same time remove excess desulfurization slag and control the remaining slag amount to ≤30mm.
[0087] In the RH process: after the RH enters the station, it is vacuumed to ≤100Pa and the vacuum is maintained for ≤10min before breaking the air. After breaking the air, it is soft-blown for 15-25min. The soft-blowing effect is based on the slag surface not being blown open. Then it is left to stand for about 10min, and then it is hoisted to the continuous casting for casting.
[0088] In the continuous casting process: the superheat is controlled at 15-30°C, the taper of the crystallizer is controlled between 1.0-1.3%, and the continuous casting billet drawing speed is between 1.0-1.5m / min. The chemical composition content of the obtained billets is shown in Table 1-1, Table 1-2 and Table 1-3.
[0089] (2) Hot rolling and coiling: The slab is heated to 1200-1260°C, and then rough rolled and finished rolled at a temperature of 850-950°C. After rolling, the slab is water cooled to a coiling temperature of 580-660°C.
[0090] (3) Pickling to remove iron oxide scale.
[0091] (4) Cold rolling: using a reduction of 50-70%.
[0092] (5) Continuous annealing: After keeping the annealing temperature at 760-820°C for 60-200s, cool to the rapid cooling start temperature of 650-690°C at a first cooling rate of 3-10°C / s to obtain a certain proportion of ferrite; then cool to the rapid cooling end temperature of 220-260°C at a second cooling rate of 40-80°C / s; then keep the temperature for 200-400s for aging treatment; finally cool to below 100°C at a third cooling rate of 2-10°C / s.
[0093] Table 1-1. (wt%, the balance is Fe and other inevitable impurities except P, S, Sn)
[0094]
[0095]
[0096] Table 1-2. (wt%, the balance is Fe and other inevitable impurities except P, S, Sn)
[0097]
[0098] Table 1-3. Composition control coefficient
[0099]
[0100] Note: In Table 3, Hem=Sn+N / 2+2S, Ceq=C+Mn / 20+Si / 30+2P+4S, where each chemical element is substituted with its mass percentage.
[0101] The steel types AE in Table 1-1, Table 1-2 and Table 1-3 are the steel type numbers used in the embodiments of the present invention, and ac are the steel type numbers used in the comparative examples.
[0102] Table 2-1 and Table 2-2 list the specific process parameters of each embodiment of the present invention and the comparative example in the above process steps.
[0103] Table 2-1.
[0104]
[0105]
[0106] Note: The “-” in the scrap steel weight ratio column of Comparative Example 1 indicates that it does not adopt the electric furnace all-scrap steel smelting process, but still adopts the converter steelmaking process and uses conventional blast furnace molten iron.
[0107] Table 2-2.
[0108]
[0109]
[0110] The obtained samples of Examples 1-20 and Comparative Examples 1-3 were corroded with 4% nitric acid alcohol solution on the polished and bright surfaces without obvious scratches, and the corrosive liquid was wiped with a clean laboratory cotton ball for about 15 seconds to observe the microstructure. The white and bright areas in the microstructure are ferrite structures, and the fine and dark structures are martensite structures. The observation results are listed in Table 3.
[0111] also Figure 1 The microstructure morphology of the ultra-high strength steel with low carbon footprint of Example 7 of the present invention is also shown. Figure 1As shown, the microstructure of the ultra-high strength steel with a low carbon footprint is ferrite + martensite.
[0112] In addition, the samples of Examples 1-20 and Comparative Examples 1-3 were subjected to ISO 6892:1998 (Room Temperature Tensile Test Method for Metallic Materials) and P14 (A 50 ) The tensile specimen standard was used for mechanical property testing and carbon footprint calculation, and the test results are listed in Table 3. The product carbon footprint calculation boundary is from cradle to gate, and the specific calculation method and product classification comply with ISO14067 "Greenhouse Gas-Product Carbon Footprint-Quantitative Requirements and Guidelines" and CISA EPD Platform PCR 2022:01 "Ordinary Steel Products and Special Steel Products".
[0113] Table 3.
[0114]
[0115]
[0116] As can be seen from Table 3, Examples 1-20 of the present invention have obtained ideal organizational characteristics through reasonable chemical element composition design combined with optimized process parameters. While ensuring strength, the plasticity performance is very excellent, the yield strength is between 700-850MPa, the tensile strength is greater than or equal to 982MPa, the uniform elongation is greater than 6%, the elongation at break is greater than or equal to 10.3%, and the performance of 180-degree cold bending is very excellent, which can meet the requirement of no cracking under 1T conditions.
[0117] It can also be seen that the carbon footprint levels of Examples 1-20 of the present invention are all less than or equal to 1.2 kgCO2eq / kg, with low carbon emission levels, meeting the technical requirements of green and low carbon. However, the process path of Comparative Example 1 still uses the conventional converter path to use blast furnace molten iron, so its carbon footprint is relatively high.
[0118] Different from the present invention, the comparative examples cannot achieve the technical effects that the present invention can achieve because the ingredients or process parameters do not meet the design requirements of the present invention.
[0119] It should be noted that the combination of the various technical features in this case is not limited to the combination described in the claims of this case or the combination described in the specific embodiments. All technical features recorded in this case can be freely combined or combined in any way unless there is a contradiction between them.
[0120] It should also be noted that the above-listed embodiments are only specific embodiments of the present invention. Obviously, the present invention is not limited to the above embodiments, and similar changes or modifications made therewith can be directly derived or easily associated with the contents disclosed by those skilled in the art from the present invention, and all should belong to the protection scope of the present invention.
Claims
1. An ultra-high strength steel with a low carbon footprint, comprising Fe and unavoidable impurities, characterized in that: It also contains the following chemical elements in the following mass percentages: C: 0.06-0.12%, Si: 0.2-0.6%, Mn: 1.7-2.3%, Mo: 0.14-0.22%, Nb: 0.02-0.05%, Ti: 0.03-0.07%, Al: 0.02-0.06%, B: 0.001-0.003%, N: 0.005-0.01%; N distribution coefficient in the ultra-high strength steel: N 固溶 / N 析出 ≥4.
2. The ultra-high strength steel according to claim 1, characterized in that: The mass percentage of each chemical element is: C: 0.06-0.12%, Si: 0.2-0.6%, Mn: 1.7-2.3%, Mo: 0.14-0.22%, Nb: 0.02-0.05%, Ti: 0.03-0.07%, Al: 0.02-0.06%, B: 0.001-0.003%, N: 0.005-0.01%; the balance is Fe and inevitable impurities.
3. The ultra-high strength steel according to claim 1 or 2, characterized in that: It also contains residual elements of at least one of the following: Cr≤0.05wt%; Ni≤0.05wt%; Cu≤0.1wt%; V≤0.05wt%.
4. The ultra-high strength steel according to claim 1 or 2, characterized in that: Among its inevitable impurities, P≤0.015%, S≤0.003%, and Sn≤0.01%.
5. The ultra-high strength steel according to claim 4, characterized in that: Its harmful element factor Hem≤0.018%, wherein Hem=Sn+N / 2+2S, and each chemical element is substituted into its mass percentage.
6. The ultra-high strength steel according to claim 4, characterized in that: Its welding carbon equivalent Ceq≤0.28%, Ceq=C+Mn / 20+Si / 30+2P+4S, where each chemical element is substituted into its mass percentage.
7. The ultra-high strength steel according to claim 1 or 2, characterized in that: The mass percentage of each chemical element further satisfies at least one of the following items: C:0.08-0.11%; Si: 0.3-0.6%; Mn: 1.9-2.1%; Mo: 0.16-0.20%; Nb: 0.025-0.045%; Ti: 0.04-0.06%; Al:0.02-0.05%; B:0.002-0.003%。 8. The ultra-high strength steel according to claim 1 or 2, characterized in that: Its microstructure includes ferrite and martensite.
9. The ultra-high strength steel according to claim 8, characterized in that: The volume phase ratio of martensite is 60-75%.
10. The ultra-high strength steel according to claim 1 or 2, characterized in that: Its yield strength is 700-850MPa, tensile strength is ≥980MPa, elongation at break is ≥10%, 180-degree cold bending performance ensures no cracking under 1T conditions, and carbon footprint is ≤1.2kgCO2eq / kg.
11. The method for producing ultra-high strength steel with a low carbon footprint according to any one of claims 1 to 10, characterized in that: It includes the steps of: Use all scrap steel for electric furnace smelting, LF, RH and continuous casting; in the RH process, the vacuum treatment time is ≤10min, and the soft blowing after breaking the air is 15-25min; Hot rolling and coiling; Cold rolling; Continuous annealing: first keep the annealing temperature at 760-820℃ for 60-200s, then cool to the rapid cooling start temperature of 650-690℃ at the first cooling rate of 3-10℃ / s, then cool to the rapid cooling end temperature of 220-260℃ at the second cooling rate of 40-80℃ / s, then keep for 200-400s for aging treatment, and finally cool to 100℃ or below at the third cooling rate of 2-10℃ / s.
12. The manufacturing method according to claim 11, characterized in that: In the electric furnace smelting process, the scrap steel used includes three types of light scrap steel, medium scrap steel and heavy scrap steel, and the weight ratio of them is light scrap steel: medium scrap steel: heavy scrap steel = (3-3.5): (1.5-2):
1.
13. The manufacturing method according to claim 11, characterized in that: In the LF process, the slag basicity is 1.8-2.5 to remove the S content to less than 30ppm.
14. The manufacturing method according to claim 11, characterized in that: In the continuous casting process, the superheat is controlled to be ≤30°C, the taper of the crystallizer is controlled to be 1.0-1.3%, and the continuous casting billet drawing speed is controlled to be 1.0-1.5m / min.
15. The manufacturing method according to claim 11, characterized in that: In the hot rolling step, the slab heating temperature is controlled to be 1200-1260°C, and the finishing rolling temperature is controlled to be 850-950°C.
16. The manufacturing method according to claim 11, characterized in that: In the coiling step, the coiling temperature is controlled to be 580-660°C.
17. The manufacturing method according to claim 11, characterized in that: In the cold rolling step, the cold rolling reduction ratio is controlled to be 50-70%.
Citation Information
Patent Citations
Cold-rolled high-strength steel with tensile strength of more than 1500 Mpa and excellent formability and manufacturing method thereof
CN108018484A
800MPa-grade cold-rolled hot-galvanizing dual-phase steel and production method thereof
CN109097705A
Ultrahigh-strength dual-phase steel and manufacturing method thereof
CN113737087A
Method for smelting low-sulfur, low-aluminum and high-carbon steel for wire rod by full waste steel electric furnace
CN115058641A
High tensile cold-rolled steel sheet excellent in ductility and in strain ageing hardening properties, and method for producing same
CN1383458A